Statistical Processing of Field Data to Predict Additional Production after the Use of Conformance Control Technology - Gilmanov, A.; Shevelev, A. (Theoretical foundations of chemical engineering, 2024)
Currently, a considerable number of wells in the oil fields in the world are subject to high production water cut. With layered heterogeneity of the formation, the conformance control technology is used, the modelling of which allows optimizing the injection volumes of reagents. For the completeness of the analysis, it is necessary to use field data on producing wells. The aim of the work is to select criteria for filtering the analyzed data for interpreting the curves of oil production decline, since these data may have significant noise. The experience of applying the conformance control technology in several fields in Western Siberia is considered. Filtering of field data by producing wells was implemented using the Kalman filter. An algorithm for interpreting the curves of oil production decline is proposed and tested. Treatment with a suspension system of one of the injection wells showed a qualitative confirmation of the proposed ideas.